KAJIAN STRATEGI PENGEMBANGAN TEMPAT PELELANGAN IKAN (TPI) KOTA PEKALONGAN - Sabana, Choliq; Madusari, Benny Diah; Praktikwo, Suryo (JURNAL LITBANG KOTA PEKALONGAN, 2016)
PEKALONGAN CITY'S DEVELOPMENT IS INSEPARABLE FROM THE EXISTENCE OF THE FISH AUCTION (TPI) IN A HISTORICAL TPI PEKALONGAN CITY HAD TRIUMPHED IN THE '80S UNTIL ITS PEAK IN 1994 WHEREAS IN 1994 TPI ACHIEVED HIGHEST EVER PRODUCTION OF UP P103.008 TONNES WORTH RP 62.228 BILLION, A LOT OF THINGS THAT LED TO THE ACQUISITION OF HIGH PRODUCTION, SUCH AS THE OWNERSHIP OF THE VESSEL BY THE ORIGIN PEKALONGAN TO REACH THE NUMBER OF 700 UNITS, THE NUMBER OF SHIPS FROM OTHER REGIONS WHO WANT UNLOADING IN TPI CITY OF PEKALONGAN, THE AUCTION SYSTEM IN CASH, AND VARIOUS FACILITIES TPI ADEQUATE. AFTER 1994 PRODUCTION LEVELS GRADUALLY DECLINE AND FLUCTUATE. BASED SOURCES PPNP IN 2013 THAT DURING 2003 S / D IN 2012 FISH PRODUCTION LEVELS FELL AN AVERAGE OF 10%. LOWEST PRODUCTION IN 2010 ONLY REACHED 18.523 TONS, WORTH 120.997 BILLION. THESE CONDITIONS PRESUMABLY BECAUSE OF THE TIGHT RULES THAT ARE APPLIED BY THE CAPTURE OF THE PORT OF THE ARCHIPELAGO PEKALONGAN, AND THE EMERGENCE OF RULES THAT PROHIBIT VESSELS OVER 30 GROSS TONE BUY DIESEL SUBSIDY. RESTORE THE DOMINANCE OF THE FISHERIES SECTOR HAS AN IMPORTANT MEANING FOR THE CITY AUTHORITIES AND URBAN COMMUNITIES PEKALONGAN. THE DOMINANCE OF THE FISHERIES SECTOR SIGNIFICANTLY INCREASED ECONOMIC ACTIVITY, ECONOMIC GROWTH AND INCREASED EMPLOYMENT OPPORTUNITIES AND OF COURSE FOR THE GOVERNMENT WOULD INCREASE THE COFFERS OF REVENUE (PAD) PEKALONGAN CITY. THIS RESEARCH IS INTENDED TO LOOK AT THE PERFORMANCE OF THE MANAGEMENT OF TPI, INTERNAL FACTORS AND EXTERNAL FACTORS TPI ANALYSIS TOOL IMPORTANCE PERFORMACE ANALYSIS (IPA) AND SWOT WAS THEN USED AS THE BASIS FOR THE FORMULATION OF DEVELOPMENT STRATEGIES TPI PEKALONGAN CITY. THE RESULTS OF THE ANALYSIS CONCLUDED THAT THE MANAGEMENT OF TPI IPA PEKALONGAN CITY INDICATE SUITABILITY LEVEL OF 73% OR IN THE CATEGORY WAS SATISFACTORY. KESESUAI HIGHEST ATTRIBUTES ARE THE ATTRIBUTES OF FISH PRODUCTS IS THE CONCORDANCE RATE OF 87% AND THE LOWEST LEVEL ATTRIBUTES KESESUAINYA IS DISCIPLINE AND FAIRNESS OF FEES. WHILE THE RESULTS OF THE ANALYSIS SWOT TPI PEKALONGAN CITY ARE IN QUADRANT II OR QUADRANT COMPETITIVE.